ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP INDUSTRI RUMAH TANGGA RENDANG KERANG DI KECAMATAN BANGKO KABUPATEN ROKAN HILIR PROVINSI RIAU - Ufira Isbah; Bunga Chintia Utami; Risa Maryu Agusta (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2023)
The problem in this study, despite the Covid-19 pandemic at the end of 2019, in Bangko Rokan Hilir District, the food industry has not decreased according to industry and trade service data for 2021. One of the food industries that has become a typical souvenir in Bangko is shellfish rendang, so did the clam rendang home industry experience a difference between the period and before Covid-19. The research variables are income, total production, profit, number of workers. And the purpose of this research is to analyze income, production amount, profit, number of workers of clam rendang production before and during the Covid-19 pandemic. The research method in this study is a quantitative method, with the types of data used are primary and secondary data. The calculation method uses the T-test. The results of this study indicate that there are differences in the amount of production, income and profit in the mussel rendang home industry before and during the Covid-19 pandemic in Bangko District, Rokan Hilir Regency, Province Riau. This is evidenced by the paired T-test that for the 3 variables Ho is rejected, which means that there is a difference in before and during the Covid-19 period. While the variable, namely the number of workers before and during the Covid-19 pandemic, were not influenced by circumstances.